Alanyl-glutamine and glutamine plus alanine supplements improve skeletal redox status in trained rats: Involvement of heat shock protein pathways - Petry, E.; Cruzat, Vinicius; Heck, T.; Leite, J.; de Bittencourt Jr, P.; Tirapegui, J. (Elsevier, 2014)
Aims: We hypothesized that oral L-glutamine supplementations could attenuate muscle damage and oxidative stress, mediated by glutathione (GSH) in high-intensity aerobic exercise by increasing the 70-kDa heat shock proteins (HSP70) and heat shock factor 1 (HSF1). Main methods: Adult male Wistar rats were 8-week trained (60-min/day, 5 days/week) on a treadmill. During the last 21 days, the animals were supplemented with either L-alanyl-L-glutamine dipeptide (1.5 g/kg, DIP) or a solution containing the amino acids L-glutamine (1 g/kg) and L-alanine (0.67 g/kg) in their free form(GLN + ALA) or water (controls). Key findings: Plasma from both DIP- and GLN + ALA-treated animals showed higher L-glutamine concentrations and reduced ammonium, malondialdehyde, myoglobin and creatine kinase activity. In the soleus and gastrocnemius muscle of both supplemented groups, L-glutamine and GSH contents were increased and GSH disulfide (GSSG) to GSH ratio was attenuated (p < 0.001). In the soleus muscle, cytosolic and nuclear HSP70 and HSF1 were increased by DIP supplementation. GLN + ALA group exhibited higher HSP70 (only in the nucleus) and HSF1 (cytosol and nucleus). In the gastrocnemius muscle, both supplementations were able to increase cytosolic HSP70 and cytosolic and nuclear HSF1. Significance: In trained rats, oral supplementation with DIP or GLN + ALA solution increased the expression of muscle HSP70, favored muscle L-glutamine/GSH status and improved redox defenses, which attenuate markers of muscle damage, thus improving the beneficial effects of high-intensity exercise training.